2001
DOI: 10.1590/s1413-86702001000200007
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of childhood community acquired pneumonia and its implications for vaccination

Abstract: Pneumonia is an important cause of morbidity and mortality among children throughout the world. Vaccines are available for some organisms, but they are underutilized and/or still in development. To evaluate the potential impact of vaccines, we review studies in which the etiology of childhood community-acquired pneumonia was recorded. In North America and Europe (9 studies), the etiology of pneumonia was established in 62% of studied children (range 43%-88%) by use of noninvasive specific methods for microbiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 52 publications
0
37
0
5
Order By: Relevance
“…Figura 1 -Algoritmo para diagnóstico e tratamento de crianças e adolescentes com faringoamidalite aguda 28 Aspectos clínicos e epidemiológicos Para os pacientes com pneumonia, OMA e SAB, os agentes etiológicos bacterianos mais freqüentes são Streptococcus pneumoniae, Haemophilus influenzae e Moraxella catarrhalis 22,29,30 . Entre os pacientes com pneumonia, a importância da etiologia bacteriana se deve à letalidade desses agentes 31 .…”
Section: Uso De Antibióticos Em Infecções De Vias Aéreasunclassified
See 1 more Smart Citation
“…Figura 1 -Algoritmo para diagnóstico e tratamento de crianças e adolescentes com faringoamidalite aguda 28 Aspectos clínicos e epidemiológicos Para os pacientes com pneumonia, OMA e SAB, os agentes etiológicos bacterianos mais freqüentes são Streptococcus pneumoniae, Haemophilus influenzae e Moraxella catarrhalis 22,29,30 . Entre os pacientes com pneumonia, a importância da etiologia bacteriana se deve à letalidade desses agentes 31 .…”
Section: Uso De Antibióticos Em Infecções De Vias Aéreasunclassified
“…Entre os pacientes com pneumonia, a importância da etiologia bacteriana se deve à letalidade desses agentes 31 . Uma compilação de estudos realizados em países desenvolvidos para investigar a etiologia da pneumonia em crianças, utilizando métodos específicos e não invasivos, mostrou que, nos pacientes nos quais foi possível determinar a etiologia, essa foi viral em 69% e 48% e bacteriana em 61% e 65% dos indivíduos hospitalizados ou ambulatoriais, respectivamente 30 . A Organização Mundial da Saúde (OMS) estima que até 1 milhão de crianças menores de 5 anos morrem anualmente de pneumonia, meningite ou sepse pneumocócica, sendo a grande maioria desses óbitos atribuída à pneumonia em países em desenvolvimento 32 .…”
Section: Uso De Antibióticos Em Infecções De Vias Aéreasunclassified
“…27 The bacterial etiologic agents most common among patients with pneumonia, AOM and ABS are Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis. 22,29,30 Among pneumonia patients the significance of bacterial etiology is due to the lethality of these agents. 31 A compilation made of studies undertaken in developed countries to investigate the etiology of pneumonia in children, using specific and noninvasive methods, showed that, for those patients where it was possible to determine etiology, the cause was viral in 69%…”
Section: Use Of Antibiotics For Airway Infectionsmentioning
confidence: 99%
“…1 The main aetiology behind Community acquired pneumonia are Viral and bacterial pathogens. 2 In a country like India, the empirical use of antibiotics is routine because of the association between bacterial infection and childhood deaths attributable to CAP, there is a need to formulate various strategies to determine the underlying pathogen causing the disease and tests for early diagnosis and differentiation between viral and bacterial causes of CAP. 3,4 All over the world, it has been seen the viral infections among children with CAP are more frequent than bacterial infections.…”
Section: Introductionmentioning
confidence: 99%